2007
DOI: 10.1109/tcsii.2007.894428
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Mode Power Gating Structure for Low-Voltage Deep-Submicron CMOS ICs

Abstract: Most existing power gating structures provide only one power-saving mode. We propose a novel power gating structure that supports both a cutoff mode and an intermediate powersaving and data-retaining mode. Experiments with test structures fabricated in 0.13-m CMOS bulk technology show that our power gating structure yields an expanded design space with more powerperformance tradeoff alternatives. Index Terms-Deep-submicrometer CMOS, ground bounce noise, low voltage, multi-threshold CMOS (MTCMOS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 18 publications
(14 reference statements)
0
49
0
Order By: Relevance
“…While PU6 is near the center of the chip and has lower peak noise of around 160 mV. Kim et al reported similar observations in [38] that the power gating induced P/G noise for a small circuit of two linear-feedback shift registers and a 32-bit carry look-ahead adder fabricated with 130 nm technology is already about 9 percent of the supply voltage and becomes a reliability threat in low power circuit design. Different impact ranges can be observed in Fig.…”
Section: The Physical Model Of Power Gating-induced P/g Noisymentioning
confidence: 68%
“…While PU6 is near the center of the chip and has lower peak noise of around 160 mV. Kim et al reported similar observations in [38] that the power gating induced P/G noise for a small circuit of two linear-feedback shift registers and a 32-bit carry look-ahead adder fabricated with 130 nm technology is already about 9 percent of the supply voltage and becomes a reliability threat in low power circuit design. Different impact ranges can be observed in Fig.…”
Section: The Physical Model Of Power Gating-induced P/g Noisymentioning
confidence: 68%
“…Because of the self-inductance of the off-chip bonding wires and the parasitic inductance inherent to the on-chip power rails, these surges result in voltage fluctuations in the power rails. If the magnitude of the voltage surge or droop is greater than the noise margin of a circuit, that circuit may erroneously latch to the wrong value or switch at the wrong time [7][8]10]. Inductive noise, also known as simultaneous switching noise, is a phenomenon that has been traditionally associated with input/output buffers and internal circuitry.…”
Section: Ground Bounce Noise Reductionmentioning
confidence: 99%
“…Without a clear understanding of the technique, however, the negative effects of power gating, such as, inductive noise and the range of device options, make it difficult to realize the potential benefits. Ground bounce is induced by an instantaneous power mode transition of a sleep transistor in a power gating structure [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…To preserve the data in the circuit block during idle periods, an intermediate data retention mode is required. Many power gating techniques [6][7][8][9] have been proposed for leakage reduction and data retention. In all these techniques, the charge gets stored at the gate of the sleep transistor during active mode.…”
Section: Introductionmentioning
confidence: 99%